1998
DOI: 10.1016/s0014-5793(98)00394-9
|View full text |Cite
|
Sign up to set email alerts
|

Flash‐induced voltage changes in halorhodopsin from Natronobacterium pharaonis

Abstract: The flash-induced voltage response of halorhodopsin at high NaCl concentration comprises two main kinetic components. The first component with d dW1 W Ws does not exceed 4% of the overall response amplitude and is probably associated with the formation of the L (hR520) intermediate. The second main component with d dW1^2.5 ms which is independent of Cl 3 concentration can be ascribed to the transmembrane Cl 3 translocation during the L intermediate decay. The photoelectric response in the absence of Cl 3 has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…Moreover, as a necessary adaptation to small cell volume and genome size, microbes carry out sensation, transduction, and action via highly compact mechanisms, often all encompassed within a single open genetic reading frame (as with the microbial opsins, in which both photon sensation and ion flux effector function are implemented within a single compact protein) (Kalaidzidis et al, 1998; Lanyi and Oesterhelt, 1982; Lozier et al, 1975; Nagel et al, 2003). In contrast, metazoan or vertebrate cells may transduce energy or information with more complex multicomponent signaling cascades that afford greater opportunities for modulation but are much less portable (as with the vertebrate opsins).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as a necessary adaptation to small cell volume and genome size, microbes carry out sensation, transduction, and action via highly compact mechanisms, often all encompassed within a single open genetic reading frame (as with the microbial opsins, in which both photon sensation and ion flux effector function are implemented within a single compact protein) (Kalaidzidis et al, 1998; Lanyi and Oesterhelt, 1982; Lozier et al, 1975; Nagel et al, 2003). In contrast, metazoan or vertebrate cells may transduce energy or information with more complex multicomponent signaling cascades that afford greater opportunities for modulation but are much less portable (as with the vertebrate opsins).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, FTIR spectroscopy suggested structural similarity between the O intermediate and the anion-free unphotolyzed state [17]. However, the previous flashinduced voltage measurements led to the conclusion that O does not appear in the Cl − transport photocycle [18]. On the other hand, other voltage measurements detected large electrogenicity during O formation [15,19].…”
Section: Introductionmentioning
confidence: 91%
“…Although it had been known that microbial opsins can control membrane potential in their native settings and various reduced systems (e.g., Ehrlich et al, 1984;Kalaidzidis et al, 1998;Nagel et al, 2002Nagel et al, , 2003, the surprising ability of these proteins when heterologously expressed to precisely control neurons and the technology for applying these tools in freely behaving animals have been demonstrated only over the past two years (for review, see Zhang et al, 2007b). ChR2 was the first microbial opsin brought to neurobiology, where it was initially found in hippocampal neurons that ChR2-expressing neurons can fire blue lighttriggered action potentials with millisecond precision, as a result of depolarizing cation flux, without addition of chemical cofactors (Boyden et al, 2005).…”
Section: Channelrhodopsin-2 (Chr2) and Halorhodopsin (Nphr)mentioning
confidence: 99%
“…Wang et al, 2007;Zhang and Oertner, 2007). Second, an inhibitory member of the microbial opsin family (Ehrlich et al, 1984;Hegemann et al, 1985;Duschl et al, 1988;Bamberg et al, 1993;Kalaidzidis et al, 1998;Kolbe et al, 2000) was brought to neurobiology; in work stimulated by the finding that the all-trans retinal chromophore required by microbial opsins appears already present within mammalian brains (Zhang et al, 2006), it was found that neurons targeted to express the light-activated chloride pump halorhodopsin from Natronomonas pharaonis (NpHR) can be hyperpolarized and inhibited from firing action potentials when exposed to yellow light in intact tissue and behaving animals (Zhang et al, 2007a); because of the excitation wavelength difference, the two optical gates can be simultaneously used in the same cells even in vivo (Zhang et al, 2007a) and may modulate aspects of neural synchrony with high temporal precision (Han and Boyden, 2007) (for review, see Zhang et al, 2007b). Third, genetic targeting tools have been developed for versatile use of microbial opsins with existing resources including cell type-specific promotor fragments or Cre-LoxP mouse driver lines suitable for a wide variety of neuroscience investigations (Adamantidis et al, 2007;Zhang et al, 2007a,c;described below).…”
Section: Channelrhodopsin-2 (Chr2) and Halorhodopsin (Nphr)mentioning
confidence: 99%